The Quasi-Judicial Role of Hakam in Malay Customary Justice of Jambi as an Alternative Dispute Resolution - Kurniawan, Ardian (Gemini Littera Publishing, 2026)
This article examines the position and role of hakam within the Jambi Malay customary justice system, with particular emphasis on their function as a form of quasi-judicial authority and as an alternative dispute resolution (ADR) mechanism within Indonesia’s plural legal system. Previous studies on customary law and dispute resolution have largely framed adat as a cultural normative system, while paying limited attention to the adjudicative functions exercised by customary actors operating outside the formal structure of state courts. Employing a socio-legal research approach with a qualitative juridical-empirical design, this study draws on in-depth interviews with customary leaders and hakam in Jambi Province, complemented by doctrinal analysis and a review of relevant academic literature. The findings reveal that hakam perform substantive judicial functions, including fact-finding, interpretation of customary and religious norms, the issuance of socially binding decisions, and the imposition of sanctions grounded in community norms. These practices position hakam not merely as mediators, but as legal actors exercising limited adjudicative authority within a non-state legal framework. The article argues that recognizing hakam as a quasi-judicial form of ADR enriches contemporary debates on legal pluralism and challenges state-centric conceptions of justice. From a normative perspective, the study recommends a model of recognition and coordination between state law and customary justice to enhance access to justice without undermining the social legitimacy of customary institutions.